2012
DOI: 10.1002/qua.24216
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical estimation of the acidities of alcohols and azoles in gas phase, DMSO, and water

Abstract: Most acidities and basicities of chemical compounds are measured in aqueous solution since this solvent is most important for biochemical and environmental applications, but the acidities of compounds in the gas phase and in other solvents can also be of interest. As a polar, aprotic solvent, dimethyl sulfoxide (DMSO) presents a unique environment for acid dissociation, and this solvent offers informative comparisons with both the vacuum and aqueous environments. Here, quantum chemical approaches previously us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
(53 reference statements)
0
18
0
Order By: Relevance
“…The pK a depends strongly on the solvent employed, since solvation of the species engaged in the dissociation process plays a crucial role, and experimental pK a s have been measured in a wide variety of solvents . Bordwell, e.g., has extensively studied the pK a s of compounds in DMSO, and others have compared acidities in different solvents . A number of popular theoretical solvent models, such as the SMX series of Cramer, Truhlar, and their coworkers and the COSMO model of Klamt and coworkers, can be applied to both aqueous and nonaqueous solvents.…”
Section: Further Commentsmentioning
confidence: 99%
“…The pK a depends strongly on the solvent employed, since solvation of the species engaged in the dissociation process plays a crucial role, and experimental pK a s have been measured in a wide variety of solvents . Bordwell, e.g., has extensively studied the pK a s of compounds in DMSO, and others have compared acidities in different solvents . A number of popular theoretical solvent models, such as the SMX series of Cramer, Truhlar, and their coworkers and the COSMO model of Klamt and coworkers, can be applied to both aqueous and nonaqueous solvents.…”
Section: Further Commentsmentioning
confidence: 99%
“…As for alcohols and phenols, thiols exist as different conformers (rotamers) depending on the relative orientation of the -SH group with respect to the remainder of the molecular skeleton; only parameters for the most stable conformers were used in the regression analyses. The molecular descriptors used were analogous to those used in earlier studies of alcohols and phenols [17,28,29], and are summarised in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…160 Kreye and Seybold 161 also studied the correlations between properties, such as bond lengths, and atomic charge values, that can be regarded as quantum chemical indices and the pK a of a set of phenol derivatives. Further, Seybold and Kreye 162 reported the use of the RM1 method to investigate correlations between chemical descriptors and a set of alcohols, phenols and azole compounds, in the gas phase, in dimethyl sulfoxide (DMSO) and in aqueous solutions. The authors mentioned: "The semiempirical RM1 method generally acquitted itself well for the alcohols and phenols.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…For the azoles, this method did not yield strong fits for the gas-phase acidities, but performed well for the pK a s in DMSO and water". 162 Furthermore, Ugur et al 163 reported the use of RM1 to predict atomic charge descriptors that were correlated with pK a values of a set of compound alcohols and thiols, and employed this strategy to predict the values of pK a s for a set of amino acids.…”
Section: Analytical Chemistrymentioning
confidence: 99%